"I Just Decided to Stop:" Understanding PrEP Discontinuation Among Individuals Initiating PrEP in HIV Care Centers in Kenya. (1st May 2021) - Ongolly, Fernandos K.; Dolla, Annabel; Ngure, Kenneth; Irungu, Elizabeth M.; Odoyo, Josephine; Wamoni, Elizabeth; Peebles, Kathryn; Mugwanya, Kenneth; Mugo, Nelly R.; Bukusi, Elizabeth A.; Morton, Jennifer; Baeten, Jared M.; et al.
Abstract : Background: Preexposure prophylaxis (PrEP) discontinuation rates in clinical trials and demonstration projects have been well characterized; however, little is known about discontinuation in routine public health settings in sub-Saharan Africa. Understanding discontinuation in nonstudy settings is important for establishing expectations for PrEP continuation in national programs and for facilitating effective PrEP scale-up. Methods: We conducted in-depth interviews with 46 individuals who had initiated PrEP at 25 HIV comprehensive care clinics (CCCs) in central and western Kenya and whose clinic records indicated they had discontinued. Results: Many of our study participants discontinued PrEP when their perceived risk decreased (eg, hiatus or end of a sexual relationship or partner known to be living with HIV became virally suppressed). Others reported discontinuation due to side effects, daily pill burden, preference for condoms, or their partner's insistence. Participant narratives frequently described facility level factors such as stigma-related discomforts with accessing PrEP at CCCs, inconvenient clinic location or operating hours, long wait times, and short refill dates as discouraging factors, suggesting actionable areas for improving PrEP access and continuation. Conclusion: Clients frequently make intentional decisions to discontinue PrEP as they weigh different prevention options within the context of complex lives. Many clients will decide to discontinue PrEP when perceiving themselves to be at reduced risk and PrEP counseling must include provisions for addressing seasons of risk. PrEP will not be the right prevention method for everyone, or forever. Expanding PrEP access points and increasing sex-positive messaging may facilitate PrEP being a better option for many.